STRUCTURAL STRENGTH ANALYSIS AND EXPERIMENTAL RESEARCH FOR WORKING DEVICE OF LOADER - WAN YiPin; JIA Jie; LIANG Jia; SONG XuDing (Jixie qiangdu)
In order to obtain the positions of load spectrum measuring points of the loader working device,the structural strength and fatigue strength of the working device were evaluated. The bucket force model was set up and the working device finite element model was builted. The method with typical operating conditions was used in simulation and experimental research on the structure strength analysis. The results showed that the simulation results agree well with the measured values,and the error of them between the 1. 6% 7. 3%,so as to effectively determine the load measuring point location area. Goodman fatigue limit diagram method was used to evaluate the fatigue strength of the measuring point. The results showed that the structure satisfied the requirements of fatigue strength. The static strength and fatigue strength evaluation were combined to obtain a more complete structural strength analysis method. Structural strength analysis and test results provide bases for the load spectrum test and fatigue life analysis of the loader working device.